INTERNET SEARCH INTENSITY AND FIRM VALUE: EVIDENCE FROM INDONESIA’S CONSUMER NON-CYCLICAL SECTOR (2020-2024) - Lisa; Randy Kuswanto (JAT : Journal Of Accounting and Tax, 2026)
This study addresses the critical role of digital information in capital markets by analysing the impact of Internet Search Intensity (ISI) on firm value. While traditional financial metrics are well documented, the influence of online investor attention as a proxy for market sentiment remains a growing area of inquiry, particularly in the Indonesian market. This research aims to examine the effect of ISI, measured via Google Trends, on the value of consumer non-cyclical firms listed on the Indonesia Stock Exchange from 2020 to 2024. Controlling for profitability, firm size, leverage, and institutional ownership, the study employs a quantitative approach using purposive sampling, resulting in a dataset of 390 observations from 78 firms. Multiple linear regression analysis reveals that ISI significantly influences firm value, suggesting that digital search activity shapes market perception. Furthermore, profitability and firm size positively correlate with firm value, whereas leverage shows mixed effects. These findings conclude that digital information and firm-specific characteristics are pivotal in determining market valuation in the era of information technology. This research provides essential insights for investors and corporations to better navigate the digital landscape of the Indonesian capital market.